Audit of deprivation of life through abortion: what irregularities does the Constitutional Tribunal judgment K 1/20 address? - Bernaciak, Nikodem; Gęsiak, Katarzyna; Szewczuk, Gabriela; Tarnacki, Damian (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
The purpose of this chapter is to show the immorality of the eugenic abortion procedure, its obvious non-compliance with the Constitution of the Republic of Poland, confirmed by the judgment of the Constitutional Tribunal in 2020, as well as the need to remove this premise of admissibility of abortion due to the real possibility of its abuse. The system of reporting on the reasons for abortions performed in Polish hospitals was found to be defective, including due to a lack of transparency. Until 2017, the public did not have the opportunity to know the list of conditions that the staff of a given hospital considered the basis for the decision to kill a given child. Despite significant improvements in this area, access to this data is still hampered in many ways. This situation indicates an urgent need to conduct a specific abortion audit and verify medical records after 1993 in order to check whether the law allowing abortion as an exception to the general principle of protection of life in Poland has not been abused in practice.